Street Pattern Identification for Crime Prevention through Environmental Design - Rasidah Md Sakip, Siti; Nabilah Mustafa, Anith (International Journal of Engineering and Technology, 2019)
Malaysia is one of the countries that is facing rapid urbanization. The crime rates are getting worse by the day and has become one of the threats faced by the community. The number of cases and incidents of snatch theft in Malaysia are fluctuating from the year of 2010 until the year 2015. Four major cities in Malaysia with high rates of snatch theft include Selangor, Kuala Lumpur, Penang and Johor with 5,553 cases, 4,687 cases, 1,953 cases, and 298 cases respectively. Hence, crime prevention and common crimes of opportunities such as snatch incidents should be addressed in urban planning.  This paper focuses on street pattern identification for crime prevention through environmental design.  In this study, the street pattern that are vulnerable to incidences of snatch theft have been identified using Geographic Information System (GIS).  The result confirmed that the fragmented parallel street is prone to crime as stated in the theory of street pattern.  Previous studies by other scholars found that the street with a high turning point is relatively prone to crime.  This is confirmed in this study that a high turning point is correlative with the fragmented parallel street pattern.
Keywords: CPTED; Crime; Hotspot; Snatch theft; Street Pattern.